Effects of rf Power on Chemical and Physical Structure of Polytetrafluoroethylene Thin Films - Nopporn Rujisamphan (Science Faculty of Chiang Mai University, 2019)
Polytetrafluoroethylene (PTFE) thin films were prepared by rf magnetron sputtering in argon plasma. The effects of rf power (10 to 100 W) on the chemical and physical structures of PTFE thin films were studied. X-ray photoelectron spectroscopy (XPS) results showed that small amounts of CF3 (1.75%) were observed at rf power of 10 W. At increased rf power (25-100 W), the intensities of CF2 and C-CF groups dramatically increased accompanied with water contact angle increasing from 78° to 87°. The atomic ratio of fluorine and carbon (F/C) increases from 0.36 to 1.65 with increasing rf power. Fourier transform infrared spectroscopy (FTIR) results showed the overlap of asymmetric and symmetric stretching of CF2 at all rf powers, while the C=C bonding was clearly visible at rf powers from 25 to 100 W. All PTFE thin films showed an amorphous structure and were colorless with almost 93 percent transmittance in visible wavelength.